What has happened to growth in Latin America - Morley, Samuel (International Food Policy Research Institute, 2001)
Growth in the first post-reform decade in Latin America has been disappointing, largely because of a severe slowdown after 1995 in the countries in South America. Per capita income grew at only .9% per year between 1995 and 1999 compared to 2.7% for 1950-80 and 1.5% for the nineties as a whole. What has gone wrong? The paper finds that neither falling investment, volatile capital inflows nor the implementation of structural reforms is the problem. Indeed relative growth performance across countries is positively related to the amount of reform they adopted. Instead the problem seems to relate to a significant reduction in the growth rate of exports since 1997. Mexico, Costa Rica and the Dominican Republic did well, but every country in South America has suffered a reduction in exports with the exception of Colombia where they were constant. Partly that is because the countries that are the main markets for Latin exports are not growing as fast as they were, but South America is also losing market share in those countries. The basic assumption of the new reform growth model is that exports will be a significant engine of growth. It does not seem to be working out that way for South America. It is not clear what the cause of the export slowdown is, but no export-led growth strategy is going to work if it cannot produce an export growth rate higher than 2.3% per year.